Contemporary State and Prospects of using Innovational Technologies for Detection and Investigation of Crimes in the Republic of Kazakhstan - SAMENOVA, Zarina B. (Journal of Advanced Research in Law and Economics; Vol 6 No 2 (2015): JARLE Volume VI Issue 2(12) Summer 2015, 2016)
The present article reviews innovational technologies that are used for the detection and investigation of crimes. It also defines prospects of further implementation of the contemporary scientific achievements in the activity of law enforcement authorities. One of the basic tasks of the law enforcement authorities of Kazakhstan is the increase in crime solving rate. The use of innovational technologies put into service by law enforcement authorities could considerably simplify solving this task. However, the potential that high technologies undoubtedly have is not sufficiently used in the area of crime prevention. It shows that in spite of some provision of law enforcement authorities of the Republic of Kazakhstan with advanced technologies, the reality dictates the necessity to develop proper ones and to implement innovational foreign means and technologies that allow to efficiently detect and investigate crimes in a qualitative manner. It considers basic areas of using high technologies in the law enforcement activity. It gives examples of applying innovational technologies in the western counties that allow law enforcement authorities to achieve qualitatively new levels in detection and investigation of crimes. It emphasizes the importance of educational factor in the implementation of innovational technologies. It stipulates the necessity to create a modern capable inter-institutional model of law enforcement institutions that works on the basis of the unity of education, scientific researches and practice.
Keywords: Innovational technologies, automated systems, investigation